A facile synthesis of novel binder-free NiSe-SnSe electrode: With enhanced electrochemical performance and superior life span - Khan, Afaq Ullah; Liu, Yanhong; Tahir, Kamran; Almarhoon, Zainab M.; Chen, Qitao; Zaki, Magdi E.A.; Badi, Nacer; Al-Saeedi, Sameerah I.; Mao, Baodong (Journal of energy storage, 2024)
Fossil fuels depletion and deteriorating environmental conditions have deepened the growing demand for new energy solution. The bimetallic transition metal selenides, which a smaller bandgap and greater electrical conductivity than nanometals, are the subject of recent research on hybrid supercapacitors, composite systems integrating battery-like energy storage capability with capacitive charging. Herein, a new binder NiSe-SnSe composite system for supercapacitors has been developed through facile hydrothermal method, and its structural features, morphological characteristics as well as electrochemical properties are systematically studies in this work. Additionally, a thorough understanding of the electrode physicochemical properties are presented. Practically, a NiSe-SnSe||AC|KOH ASC had excellent specific capacitance (618 F/g at 1 A g−1), mainly owing to fast charge transport in electrochemical action. More importantly, the NiSe-SnSe||AC|KOH ASC electrode exhibits a high specific power of 8400 W kg−1 at a high specific energy of 55.4 Wh kg−1 with remarkable cycling stability by 96.4 % maintenance of initial capacitance after 5500 cycles. Our findings provide a profound understanding and possible use of this newly developed asymmetric supercapacitor in energy storage. •A novel binder-free NiSe-SnSe composite was prepared by hydrothermal method.•NiSe-SnSe||AC|KOH ASC demonstrates an excellent energy density of 55.4 Wh/kg achieved at a 8400 W/kg.•NiSe-SnSe||AC|KOH ASC excellent stability of 96.4% retention after 5500 cycles.